2022
DOI: 10.1212/wnl.0000000000200699
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Association and Meta-analysis of Age at Onset in Parkinson Disease

Abstract: Background and Objectives:Considerable heterogeneity exists in the literature concerning genetic determinants of the age of onset (AAO) of Parkinson’s disease (PD), which could be attributed to lack of well-powered replication cohorts. The previous largest GWAS identified SNCA and TMEM175 loci on chromosome (Chr) 4 with a significant influence on AAO of PD, these have not been independently replicated. The present study aims to conduct a meta-analysis of GWAS of PD AAO and validate previously observed findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 44 publications
(120 reference statements)
0
21
0
Order By: Relevance
“…In the past two decades, PD etiopathogenesis has been linked with several deranged cellular mechanisms, ranging from mitochondrial impairment ( PRKN , PINK1 , PARK7 ) and ubiquitination defects ( FBXO7 ) to dysfunction of the endolysosomal pathway ( LRRK2 , VPS35 , VPS13C , ATP13A2 ) and synaptic vesicle trafficking ( SNCA , RAB39B , SYNJ1 , DNAJC6 ). In addition, significant parts of the risk genes associated with PD encode for endolysosomal and synaptic vesicle proteins, confirming a particular susceptibility of PD-related brain structures to the impairment of these pathways ( Figure 1 ) [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 76%
“…In the past two decades, PD etiopathogenesis has been linked with several deranged cellular mechanisms, ranging from mitochondrial impairment ( PRKN , PINK1 , PARK7 ) and ubiquitination defects ( FBXO7 ) to dysfunction of the endolysosomal pathway ( LRRK2 , VPS35 , VPS13C , ATP13A2 ) and synaptic vesicle trafficking ( SNCA , RAB39B , SYNJ1 , DNAJC6 ). In addition, significant parts of the risk genes associated with PD encode for endolysosomal and synaptic vesicle proteins, confirming a particular susceptibility of PD-related brain structures to the impairment of these pathways ( Figure 1 ) [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 76%
“…The TMEM175 gene is located on chromosome 4 in the TMEM175/GAK/DGKQ GWAS locus associated with PD [ 9 ]. Recently, the TMEM175 p.M393T common variant was described as a risk factor for PD in several populations [ 11 , 14 ], and rare deleterious variants were associated with PD in Italian families [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…TMEM175 , one of the novel genes identified in our cohort of PD families, is located in a highly significant PD GWAS peak at chromosome 4 [ 9 , 10 ]. Recently, two common coding variants, rs34884217 (c.A194C, p.Q65P) and rs34311866 (c.T1178C, p.M393T), have been associated with PD risk in several populations [ 11 14 ]. This gene encodes for an endolysosomal K + channel that is involved in K + conductance, pH stability, and α-synuclein clearance [ 15 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, the largest GWAS in PD, involving almost 38 thousand patients, found 90 common independent variants, which together accounted for 16–36% of the observed PD heritability ( Nalls et al, 2019 ). Recently, a large meta-analysis on PD GWAS on 8,535 patients revealed that polymorphisms of the TMEM175 (rs34311866), SNCA (rs983361), and BST1 (rs4698412) correlated with the age of the disease onset ( Grover et al, 2022 ).…”
Section: Oligo- and Polygenic Genetic Factors Behind Parkinson’s Dise...mentioning
confidence: 99%